Religious Value in Cinta Subuh Movie - Widyanto, Tyas Wulandari Putri; Sujarwoko, Sujarwoko; Sardjono, Sardjono (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
Humans, as creatures of God, have various potentials that God has given them. All human potential, especially religious potential, must constantly be developed. One way is through education. A factor that can influence education is the media. Educational media can be audiovisual media such as films. Because the messages in the film can be seen and heard simultaneously, it is easier to learn, which requires real examples. Literary works function as a channel for the author's emotions and empathy when observing an event. Belief, morals, and worship are among the religious principles depicted in Cinta Subuh. In this research, literature research uses qualitative methodology. This research uses the content analysis technique as its data analysis method. Indra Gunawan's film Cinta Subuh is the primary data source for this research. Supporting literature related to the object of this research comes in the form of secondary data sources. The research results show that Akhlak includes being patient in facing challenges, fearing Allah SWT, and treating others well to cause peace of mind. The meaning of worship includes prayer in fostering faith, getting protection from Allah SWT, and finding proper solutions to all life problems, both in the world and the hereafter.